NILAI RELIGIUSITAS DIMENSI EXPERENTIAL DALAM SYAIR SEUDATI ACEH - Subhayni, Subhayni; AR, Muhammad; Shadiqin, Sehat Ikhsan; Nurliza, Eli (Jurnal Dedikasi Pendidikan, 2025)
This study focuses on the experiential dimension of religiosity in Seudati poetry, providing constructive insights for researchers and readers regarding the experiential aspects found within its verses. Seudati poetry, as a cultural treasure of Acehnese oral tradition, deserves preservation due to its profound religious values—particularly those reflecting the consequences of an individual's beliefs, practices, experiences, and daily religious knowledge. Using a descriptive-qualitative method and a literary hermeneutic approach, the study interprets Seudati poetry as a reflection of universal truths about religiosity in the lives of the Acehnese people and Muslims globally. The analysis reveals that the experiential values in Seudati poetry include feeling close to Allah and sensing that prayers are answered, feeling grateful, having faith, being patient in facing trials, and experiencing inner peace. These findings confirm that the experiential dimension of religiosity is deeply embedded in the hearts of Muslims, especially among the people of Aceh, and serves as a meaningful way to draw closer to Allah SWT, the Lord of all creation.